Past, Present, and Future Research on the Lung Microbiome in Inflammatory Airway Disease - Caverly, Lindsay J. (Chest, 2019)
COPD, asthma, and cystic fibrosis (CF) are obstructive lung diseases with distinct pathophysiologies and clinical phenotypes. In this paper, we highlight recent advances in our understanding of relationships between clinical phenotypes, host inflammatory response, and lung microbiota in these diseases. Although COPD, asthma, and CF largely have distinct lung microbiota and inflammatory profiles, certain commonalities exist. In all three of these lung diseases, and in healthy persons, anaerobic taxa that are typically associated with oral microbiota (eg, Prevotella species, Veillonella species) are present in the airways and associated with increased host inflammatory response. Similarly, across all three diseases, members of the Proteobacteria phylum are associated with more advanced disease. Finally, we highlight challenges in translating these findings into advances in clinical care, including continued knowledge gaps regarding the causal relationships between host inflammatory response, lung microbiota, medication effects, and clinical phenotypes.